Permasalahan gizi pada anak balita pasca gempa: Studi kasus di Palu, Sigi, dan Donggala - Nurulfuadi, Nurulfuadi; Ariani, Ariani; Hartini, Diah Ayu; Aiman, Ummu; Nadila, Devi; Rahman, Aulia; Husna, Sa'adatul (Tadulako University, 2021)
Palu, Sigi, and Donggala districts experienced a 7,7 magnitude earthquake on September 28 2018. This incident was declared a national disaster. The impact of the disaster is a decrease in the nutritional status of children under five. Nutritional problems in children under five after the earthquake can be caused by paralysis of health service, lack of availability of clean water, poor environmental sanitation, infectious diseases, and lack of consumption of nutritious food. This research is a descriptive study wich to identify nutritional problems in children under five after the earthquake in Palu, Sigi, and Donggala districts. The type of data used is secondary data, including height, weight, and age. The results showed that the nutritional status of under five children based on the weight for age index were underweight 32,1% and very underweight 16,6%. Nutritional status based on the weight for height index, were malnutrition 13,7% and poor nutrition 4,9%. The nutritional status based on the height for age index were stunting 55,7%. The conclusion that the stunting is a nutritional problem with the highest prevalence after the earthquake. The health of children under five is easily influenced by food security, the environment, and the economy. The high prevalence stunting post-earthquake can be caused by job losses, damage to agricultural land and plantations, disruption of the economic system and development in the area which has an impact on low access to food for families.